Influenza virus: methods and protocols - Yamauchi, Yohei (Methods in molecular biology, 2018)
Understanding Influenza -- Clinical Diagnosis of Influenza -- Influenza A Virus Genetic Tools - From Clinical Sample to Molecular Clone -- Propagation and Titration of Influenza Viruses -- Purification and Proteomics of Influenza Virions -- Haploid Screening for the Identification of Host Factors in Virus Infection -- Phenotypic Lentivirus Screens to Identify Antiviral Single Domain Antibodies -- Deciphering Virus Entry with Fluorescently-Labeled Viral Particles -- Quantitative RT-PCR Analysis of Influenza Virus Endocytic Escape -- Single Molecule Sensitivity RNA FISH Analysis of Influenza Virus Genome Trafficking -- Correlative Light and Electron Microscopy (CLEM) and 3D Methods to Study Architecture of Virus-Infected Cells -- Correlative Light and Electron Microscopy (CLEM) of Influenza Virus Entry and Budding -- Influenza Virus-Liposome Fusion Studies using Fluorescence Dequenching and Cryo-Electron Tomography -- Metal-Tagging Transmission Electron Microscopy and Immunogold Labelling on Tokuyasu Cryosections to Image Influenza A Virus Ribonucleoprotein Transport and Packaging -- Live Imaging of Influenza Viral Ribonucleoproteins using Light-Sheet Microscopy -- Purification of Unanchored Polyubiquitin Chains from Influenza Virions -- Measurement of Influenza Virus Polymerase Activity -- In vitro models to study influenza virus and Staphylococcus aureus super-infection on a molecular level -- Infection of Cultured Mammalian Cells with Aerosolized Influenza Virus -- Animal Models in Influenza Research -- Measuring Influenza Virus Infection using Bioluminescent Reporter Viruses for in vivo Imaging and in vitro Replication Assays -- Selection of Antigenically Advanced Variants of Influenza Viruses -- Assessment of Influenza Virus Hemagglutinin Stalk-specific Antibody Responses -- Analyses of Cellular Immune Responses from Ferrets Following Influenza Virus Infection -- Parameter Estimation in Mathematical Models of Viral Infections using R -- Software for Characterizing the Antigenic and Genetic Evolution of Human Influenza Viruses -- Clinical Trials of Influenza Vaccines - Special Challenges -- The Silver Lining in Gain-of-Function Experiments with Pathogens of Pandemic Potential -- Why Do Exceptionally Dangerous Gain-of-Function Experiments in Influenza? -- How Computational Models Enable Mechanistic Insights into Virus Infection.